Social Impacts of Land Acquisition for Oil and Gas Development in Uganda - Ogwang, Tom; Vanclay, Frank (Land, 2019)
Uganda’s oil and gas sector has transitioned from the exploration phase to the development phase in preparation for oil production (the operations phase). The extraction, processing, and distribution of oil require a great deal of infrastructure, which demands considerable acquisition of land from communities surrounding project sites. Here, we examine the social impacts of project land acquisition associated with oil production in the Albertine Graben region of Uganda. We specifically consider five major oil related projects that have or will displace people, and we discuss the consequences of this actual or future displacement on the lives and livelihoods of local people. The projects are: Tilenga; Kingfisher; the East African Crude Oil Pipeline; the Kabaale Industrial Park; and the Hoima–Kampala Petroleum Products Pipeline. Our findings reveal both positive and negative outcomes for local communities. People with qualifications have benefited or will benefit from the job opportunities arising from the projects and from the much-needed infrastructure (i.e., roads, health centres, airport) that has been or will be built. However, many people have been displaced, causing food insecurity, the disintegration of social and cultural cohesion, and reduced access to social services. The influx of immigrants has increased tensions because of increasing competition for jobs. Crime and social issues such as prostitution have also increased and are expected to increase.
Keywords: Project-induced displacement and resettlement; Livelihood restoration; Local resource curse; Extractive industries and society; Social impact assessment; Business and society; Land acquisition; Landtake